Women's Life Writing, 1700-1850
X, 253 p.
Keywords: This collection discusses British and Irish life writings by women in the period 1700-1850. It argues for the importance of women's life writing as part of the culture and practice of eighteenth-century and Romantic auto/biography, exploring the complex relationships between constructions of femininity, life writing forms and models of authorship.